Cyber Security Proceedings of CSI 2015 (Advances in Intelligent Systems and Computing,, 2018)
This book comprises select proceedings of the annual convention of the Computer Society of India. Divided into 10 topical volumes, the proceedings present papers on state-of-the-art research, surveys, and succinct reviews. The volume covers diverse topics ranging from information security to cryptography and from encryption to intrusion detection. This book focuses on Cyber Security. It aims at informing the readers about the technology in general and the internet in particular. The book uncovers the various nuances of information security, cyber security and its various dimensions. This book also covers latest security trends, ways to combat cyber threats including the detection and mitigation of security threats and risks. The contents of this book will prove useful to professionals and researchers alike.